A Aplikasi Plant Growth Promoting Rhizobacteria Akar Bambu dan Mikroorganisme Lokal pada Tanaman Kedelai untuk Pengendalian Penyakit Pustul Bakteri (Xanthomonas axonopodis pv. Glycines): Application of Bamboo Root Plant Growth Promoting Rhizobacteria and Local Microorganisms in Soybean to Control of Bacterial Pustule (Xanthomonas axonopodis pv. Glycines) - Lakani, Irwan; Zakaria, Jawuh; Rosmini; Mutmainah; Jusriadi (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2025)
Application of Bamboo Root Plant Growth Promoting Rhizobacteria and Local Microorganisms in Soybean to Control of Bacterial Pustule (Xanthomonas axonopodis pv. Glycines) Xanthomonas axonopodis pv. glycines (Xag) is a pathogenic bacterium that causes pustule disease in soybean plants, leading to significant levels of damage. One of the biological control efforts against this pathogen involves the use of plant growth-promoting rhizobacteria (PGPR) and local microorganisms (MOL). This study aims to determine the effect of PGPR and MOL applications on enhancing plant growth and controlling bacterial pustule disease. The Xag JB12 isolate from the University of Jember was used as the inoculum source. PGPR from bamboo roots and MOL from fruit and vegetable waste were used as antagonistic agents against the Xag JB12 isolate. The experimental study was designed using four treatments (control, PGPR application, MOL application, and PGPR + MOL application). PGPR/MOL application was carried out through seed soaking and drenching. The results showed that the MOL treatment exhibited the lowest disease severity, which was 20.02%. The MOL treatment showed the highest disease progression rate, but the smallest area under the disease progress curve (AUDPC) compared to other treatments. The study also found that all treatments had no significant effect on plant height and leaf number variables.